2010
DOI: 10.1016/j.nuclphysb.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Gepner models (revisited)

Abstract: We reconsider a class of heterotic string theories studied in 1989, based on tensor products of N = 2 minimal models with asymmetric simple current invariants. We extend this analysis from (2, 2) and (1, 2) spectra to (0, 2) spectra with SO(10) broken to the Standard Model. In the latter case the spectrum must contain fractionally charged particles. We find that in nearly all cases at least some of them are massless. However, we identify a large subclass where the fractional charges are at worst half-integer, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 78 publications
3
46
0
Order By: Relevance
“…[1] and in this paper show that no three-chiral-generation models exist and that they only exist with the inclusion of four exotic multiplets as given in the model above. Although this was a surprising feature, it is however in line with related searches [51].…”
Section: Constraintsupporting
confidence: 84%
“…[1] and in this paper show that no three-chiral-generation models exist and that they only exist with the inclusion of four exotic multiplets as given in the model above. Although this was a surprising feature, it is however in line with related searches [51].…”
Section: Constraintsupporting
confidence: 84%
“…These authors did find examples with three families where all fractionally charged particles are at the Planck mass, but only in a fraction of 10 −5 of the chiral spectra. In Gato-Rivera and Schellekens (2010Schellekens ( , 2011a; and Maio and Schellekens (2011) a similar small fraction was seen, but examples were found only for even numbers of families. These authors also compared the total number of spectra with chiral and vector-like fractional charges, and found that in about 5% to 20% of the chiral, non-GUT spectra the fractional charges are massless, but vector-like.…”
Section: Grand Unification In String Theorymentioning
confidence: 67%
“…it is not clear which minima of GSUGRA belong to the string landscape and which to the swampland. This work can be considered as the continuation of a series of papers that started with the construction of Gepner models [20][21][22][23], their extension by the simple current technique [24,25] for constructing ACFTs [26][27][28][29][30], and the recent attempt [16] to relate some of these four-dimensional ACFTs to minima of N = 2 GSUGRA partially-broken to N = 1.…”
Section: Introductionmentioning
confidence: 99%